Pengaruh Media Flashcard Dalam Meningkatkan Daya Ingat Siswa Pada Materi Huruf Hijaiyah - Imas Marisa; Hani, Umi; Lies Dharjati (Prodi PGMI STAI Sabili Bandung, 2022)
Currently, grade I students sometimes find it difficult to understand the learning material. According to the researcher, this is because students at this age have not been confronted directly with real or contextual things. Moreover, seeing the characteristics of 1st grade elementary school children is a concrete operation, which must be faced with something real. The purpose of this study was to determine the effect of flashcard media in improving the memory skills of grade 1 students of SD Islam Terpadu Insan Mulia in learning the Al-Qur'an Hadith material